Efforts to Improve History Learning Outcomes Through Snack and Ladder Media at Class XII IPS 3 SMA Negeri 3 Medan - Siregar, Andreas; Nugraha, Muhammad Adika; Sihotang, Masniar (ALACRITY : Journal of Education, 2024)
The low value in history subjects is the background of this research, classroom action research is conducted so that students are more motivated in their learning. So that the right step in improving learning outcomes, this study uses snakes and ladders media. Results of the study produced a level student learning activities in cycle 1 = 56.14% while cycle 2 = 88.28%. This has increased. Conclusion of studenst learning cycle 1 = the percentage of completion was 39.41% with an average value of 64.11%. Furthermore, cycle 2 saw an increase in the percentage of completion of 82.35% with an average value of 79.91%. The conclusion of this study is that the use of snakes and ladders media can increase learning outcomes of history of class XII IPS 3 students of SMA Negeri 3 Medan.